Laser Ablation Dry Aerosol Printing and Novel Post-processing Technologies - Su, Weiming (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2026)
Aerosol jet printing is a promising additive manufacturing technique for flexible electronics. In the wet aerosol method, a metal nanoparticle ink is aerosolised and transported to the print head. Dry aerosol jet printing, where a metal aerosol is prepared in the printing device, may offer some advantages by avoiding the need to prepare and store the nanoparticle ink. This work presents a dry aerosol jet printing technique known as laser ablation dry aerosol printing (LADAP), developed at TCD by Prof. Lupoi and Prof. Lunney. LADAP employs pulsed laser ablation of a metal target in an inert gas atmosphere at ambient pressure, generating a vapor that condenses near the target into a mist of nanoparticles and subsequent nanoparticle agglomerates. The resulting dry aerosol is transported to a print head, where it is aerodynamically focused into a narrow jet and deposited onto a moving substrate, forming fine lines composed of weakly bound nanoparticle agglomerates. The research in this thesis involves the improvement and understanding of this emerging additive micro-manufacturing technique. Industrial deployment of LADAP requires stable, consistent, and long-duration operation, which in turn demands system-level enhancements in aerosol generation, transport, and deposition to ensure a uniform and continuous material source. In parallel, post-deposition consolidation is essential for achieving the density, mechanical strength, and functional properties required for practical applications. Initially, the ablation cell was redesigned to improve the ablation process of LADAP, specifically addressing metal deposition on the laser entrance window. Preliminary experiments were carried out on a prototype cell to investigate the effects of laser scan speed and laser power on ablation rate, deposition rate, and aerosol yield, and to provide insight into the mechanisms governing laser ablation. A key finding was the ability to control aerosol ejection direction, inspiring a new laser ablation strategy featuring with uni-directional scanning to limit particle deposition on the laser entrance window. The redesigned ablation chamber, with a reduced cross-sectional area parallel to the target surface, introduces carrier gas directed opposite to the target surface to decelerate particle ejection, thereby maintaining window cleanliness and enabling more consistent aerosol generation and improved particle transport. Building on the improved ablation cell, systematic investigations of the process parameters were conducted, enabling optimization of the LADAP process and demonstrating its potential and versatility across various manufacturing sectors. Using silver as a test material, aerosol deposits were characterized for microstructure, sintering activity, mass yield, and electrical properties to clarify the relationship between process variability and mechanisms. The process demonstrated scalability, fabricating features from 20 m fine lines to 168 m thick planar structures, and versatility across circuits, sensors, and antennas. Additionally, high-throughput single-pass printing of silver deposits up to 60 m thick was achieved. Additionally, novel post-processing techniques based on plasma sintering consolidation were explored, focusing on atmospheric pressure glow discharge (APGD) plasma and spark plasma approaches. APGD sintering enabled rapid, localized, single-pass processing with low resistivity on ceramic substrates, although further improvements in plasma stability are desirable. Spark plasma sintering employing pulsed voltage discharges offered enhanced stability through periodic polarity reversal, maintaining continuous and stable plasma. Comparative analyses of pin-type, argon-assisted, and capacitive-coupled spark plasma configurations revealed the influence of electrode geometry, plasma stability, and energy delivery on sintering performance. The argon-assisted method further improved discharge stability, while the capacitive-coupled configuration, eliminating direct electrical contact, proved effective for complex geometries. Preliminary investigations into the integration of spark plasma sintering within in situ fabrication workflows demonstrated potential for real-time consolidation, although further optimization is required to improve electrical stability and process uniformity.
APPROVED
Keywords: Additive manufacturing; Direct write printing; Laser ablation; Dry aerosol jet printing; Plasma sintering; Electrical performance